A ribbed strategy disrupts conventional metamaterial deformation mechanisms for superior energy absorption - Wang, Xinxin; Li, Xinwei; Li, Zhendong; Wang, Zhonggang; Zhai, Wei (Virtual and physical prototyping, 2024)
Enhancing energy absorption in mechanical metamaterials has been a focal point in structural design. Traditional methods often include introducing heterogeneity across unit cells. Herein, we propose a straightforward ribbed strategy to achieve exceptional energy absorption. We demonstrate our concept through modified body-centered cubic (BCC) and face-centered cubic (FCC) ribbed truss-lattice metamaterials (BCCR and FCCR). Using stainless-steel 316L samples, compression tests indicate a 111% and 91% increase in specific energy absorption (SEA) for BCCR and FCCR, respectively, along with an enhancement in compression strength by 61.8% and 40.7%. Deformation mechanisms are comprehensively elucidated through both finite element analysis and theoretical calculations. The mitigation of stress concentration at nodes, redistribution of load transfer pathways within struts, and introduction of multiple plastic hinges collectively contribute to increased energy absorption and higher compression strength. Using rein-based polymer samples, the ribbed truss-lattice metamaterials also exhibit exceptional damage tolerance, experiencing only a 15% loss in maximum strength after cyclic compression at 20% strain, while maintaining a 73% higher SEA compared to their non-ribbed counterpart. This strategy extends beyond the discussed structures, presenting itself as a generic approach to enhance plateau strength and SEA.